KORELASI ANTARA SERAPAN P TANAMAN CABAI (Capsicum annum L.) DENGAN METODE PENETAPAN P TERSEDIA TANAH ORDO INCEPTISOL SUBANG - Fahmi Aprianto; Rini Rosliani; L Liferdi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The correlation test between P uptake by plant and determination method of available P is the initial stage in the establishment of fertilizer recommendations. This study aimed to examine various extraction methods of available P in the soil and determine the appropriate P extraction method for dry acid soil (Inceptisol) used to cultivate chili crop. The study was conducted at the screen house of Indonesian Vegetable Research Institute, West Java, Indonesia from January to December 2015. A randomized block design with five treatments and five replications was set up for this experiment. The treatment of status of soil P was obtained by administering SP-36 at various doses, namely: 0X, ¼X, ½X, ¾X, and 1X, where X = 250 kg SP-36 ha-1. To obtain the desired P nutrient status, the Inceptisol soil that has been added with SP-36 fertilizer with different doses was incubated for four months. The chili seedlings were then planted on each of those soils, and the analysis of P absorption was carried out at the age of 60 days after planting. There were six extraction methods used to analyze available P in the soil, i.e. HCl 25%, Bray I, Bray II, Mechlich, Truog, and Morgan Vanema. The results showed the different response of crop on P uptake to the level of soil P nutrient status. Plant P uptake increased with the increase in soil P nutrient status. The best P extraction methods for Inceptisols for chili cultivation were HCl 25% and Mechlich with correlation coefficient values reached 0.7802 and 0.7351, respectively.